Brister i veterinär intygsskrivning : en granskning av ärenden i Veterinära Ansvarsnämnden 2000 - 2007 - Ternström Hofverberg, Lotta (SLU/Dept. of Animal Environment and Health (until 231231), 2008)
After having reviewed the cases in the Veterinary Disciplinary Board of Sweden regarding certificates year 2000 to October 2007 I have found that these cases more often than in all other cases result in disciplinary action. The punishment is to a greater extent the more serious form, i.e. warning. When I examined the reasons for imposing the punishments and the material that constituted the foundations of the reports, I came to the conclusion that the statistics above do not depend on a general lack of knowledge in the Swedish veterinary profession. A possible cause is that the demands set upon the veterinarian are exceptional and that the responsibility board has a physical object to examine (the certificate) and regulations that describe how the certificates are supposed to be formulated.